Linguistic and prosodic aspects of child-directed speech: The role of maternal child-rearing experiences. Issue 2 (3rd March 2016) - Spinelli, Maria; Fasolo, Mirco; Tagini, Angela; Zampini, Laura; Suttora, Chiara; Zanchi, Paola; Salerni, Nicoletta
Abstract: This study explored if the quality of mothers' reported child-rearing experiences influences the prosodic and linguistic features of maternal child-directed speech. Lexical, syntactic, functional and prosodic aspects of maternal speech directed towards their 24-month-old children were examined. Results showed that mothers with different child-rearing histories differed in the ways they talked to their children. Mothers who recalled the caregiving they received during childhood as characterized by high levels of care and low levels of control, used a lexically and syntactically more complex speech and expressed more positive emotions. This kind of input seems to be more attuned with the typical growing skills of two-year-old children. Implications for the study of mother–infant relationship as well as for the study of child language development are addressed.